2008
DOI: 10.1128/aac.00263-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Monitoring of Plasmodium falciparum Drug Resistance in French Guiana: a Synopsis of Continuous Assessment from 1994 to 2005

Abstract: Implemented as one arm of the malaria control program in French Guiana in the early 1990s, our laboratory has since established in vitro profiles for parasite drug susceptibility to a panel of eight antimalarials for more than 1,000 Plasmodium falciparum isolates from infected patients. The quinine-doxycycline combination was introduced in 1995 as the first-line drug treatment against uncomplicated P. falciparum malaria, replacing chloroquine, and the first-line drug combination was changed to the artemether-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 28 publications
3
44
1
Order By: Relevance
“…The in vitro susceptibility to a panel of antimalarials of 513 P. falciparum isolates collected longitudinally during the years 2000 to 2005 by our reference center has been reported (28). Similar procedures were used for 187 isolates collected in the years 2006 to…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro susceptibility to a panel of antimalarials of 513 P. falciparum isolates collected longitudinally during the years 2000 to 2005 by our reference center has been reported (28). Similar procedures were used for 187 isolates collected in the years 2006 to…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity to mefloquine decreased progressively after its introduction. Susceptibility to amodiaquine was correlated positively with susceptibility to chloroquine and more moderately with susceptibility to mefloquine or halofantrine (28).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The "Centre National de Référence de la Chimiorésistance du Paludisme" (CNRCP) at IPG regularly collects P. falciparum isolates and determines their in vitro susceptibility profiles for a panel of antimalarials using the isotopic method. 9 Entomological investigation. Two entomological surveys were organized in the village of Saü l and its surroundings from January 12-14, 2009 and from April 6-10, 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing these data to results measured from isolates collected between 1983 and 1987 (11) revealed that highly resistant parasites prevailed until about 1999. However, when chloroquine treatment was no longer recommended for P. falciparum malaria the level of resistance fell sharply, and plummeted after introduction of artemisinin combination therapies in 2002 (12,13). Pelleau et al (1) assessed the genotypes of more than 1,000 of these chloroquine-susceptible isolates: all parasites still retained the ancestral SVMNT "chloroquine-resistant" genotype!…”
mentioning
confidence: 99%